Effect of Age, Sex and Level of Surgical Difficulty on Inflammatory Complications After Third Molar Surgery - Osunde, Otasowie D. (J Maxillofac Oral Surg, 2013)
BACKGROUND: Patients’ factors such as age and sex and surgical variables such as level of difficulty have been linked with surgical outcome in third molar surgery. The aim of this study was to determine the effect of these variables on inflammatory complications in patients undergoing third molar surgery. METHODS: Patients referred to our institution for surgical extraction of their impacted lower third molar between January 2007 and December 2008 were the subjects of the study. Patients’ demographics as well as types of impaction, indication and level of difficulty based on Pederson criteria were obtained. Post operative pain, swelling and mouth opening limitation were evaluated at day 1, day 2, day 3, day 5 and 1 week after the surgery and analyzed. A p value of less than 0.05 was considered significant. RESULTS: A total of 150 patients aged 16–38 years (25.9 ± 4.47) met the inclusion criteria. Male accounted for 66 (44.0 %) while females were 84 (56.0 %), giving male to female ratio of 1:1.3. Age, sex and difficulty index had no effect on pain and trismus throughout the periods of postoperative evaluation (p > 0.05). Postoperative swelling was not affected by gender but patients above 25 years who had high scores of difficulty index had more facial swelling. CONCLUSION: The results of this study shows that age, gender and the level of surgical difficulty have no effect on pain and mouth opening limitation after third molar surgery.